STRATEGI ADAPTASI GURU DALAM MENGHADAPI PERUBAHAN GAYA BELAJAR GENERASI ALPHA DI ERA DIGITAL - Nurhalimah Siahaan; Elvi Mailani; Atika Wahyuni; Fadhilah Almas; Siti Febrianti Ritonga; Siti Khaliza Wahyunindi; Syifa Salsabila (STKIP Subang, 2026)
Generation Alpha, born after 2010, has a learning style that is responsive to technology-based visual, auditory, and kinesthetic media. In the technological era, the ability to adapt is key for teachers. This research uses a mixed method by combining quantitative and qualitative approaches. The subjects of the study consisted of 12 elementary school teachers from different schools. Data collection was conducted through a questionnaire using Google Forms, consisting of closed-ended and open-ended questions. Quantitative data was analyzed using percentages to determine respondents’ response tendencies, while qualitative data was analyzed by summarizing respondents’ answers. Furthermore, this research was supported by a literature review of relevant journals and books. This study aimed to determine teachers’ adaptation strategies in addressing changes in Generation Alpha’s learning styles in the digital age. The results showed that Generation Alpha has learning characteristics influenced by developments in digital technology, such as the ability to use technological devices from an early age and a greater interest in digital-based learning compared to conventional methods. Therefore, teachers need to implement various adaptation strategies, such as collaboration between teachers, simple blended learnin, and the gradual use of digital media. Therefore, improving teachers’ digital competencies and securing support from various parties is necessary to ensure the learning process runs effectively and aligns with the characteristics of Generation Alpha in the digital age.